Fay Sharman: The Taste of France, ’A Dictionary of French Food and Wine’ - Davidson, Alan E (Petits Propos Culinaires, 2024)
Fay Sharman: The Taste of France, ’A Dictionary of French Food and Wine’: Macmillan, London, 1982: 336 pages, numerous small line drawings, maps, some advertisements in full colour, hardback, £5.95.